Observer variability in histopathological reporting of cervical biopsy specimens. Issue 3 (March 1989) - Robertson, A J; Anderson, J M; Beck, J S; Burnett, R A; Howatson, S R; Lee, F D; Lessells, A M; McLaren, K M; Moss, S M; Simpson, J G
Abstract : Sections from 100 cervical biopsy specimens were studied by 12 consultant histopathologists to determine the robustness of the existing pathology terminology and classification. Analysis by kappa statistics showed good agreement in the diagnosis of CIN 3 and squamous carcinoma but an inability to distinguish accurately between the lesser grades of CIN. It is recommended that the classification be changed to low grade (present CIN 1 and 2) and high grade (present CIN 3) categories alone. There was very poor agreement in the identification of cellular changes associated with human papilloma virus (HPV) infection.